Potensi Minuman Fermentasi Sari Kulit Singkong (Manihot esculenta) Dengan Kultur Starter Lactobacillus plantarum B1765 Sebagai Minuman Probiotik - Maulah, Ismatul; Wikandari, Prima Retno (Unesa Journal of Chemistry, 2024)
This study aims to determine the effect of fermentation time on the microbiological (total lactic acid bacteria), chemical (pH, total titratable acid), and organoleptic (color, taste, and aroma) quality of probiotic beverage products from cassava peel juice (Manihot esculenta) with Lactobacillus plantarum B1765 starter culture which has been known to have potential as a probiotic candidate. Fermentation was carried out for 0, 12, 24, 36, 48, and 60 hours with 5% (v/v) L. plantarum B1765 starter culture at 37ºC. Total LAB count was determined using Total Plate Count method, Total Titratable Acid was determined using acid-base titration, and pH was determined using pH meter, organoleptic was tested using hedonic scale method. The results showed that the length of fermentation can increase the total lactic acid bacteria (LAB), Total Titrated Acid (TAT), and Total Flavonoids. in addition, it also affects the decrease in pH value. The results showed that 24 hours of fermentation had optimal results with total LAB reaching 3.33×107 CFU/mL CFU/mL, pH value 3.84±0.030, TAT value 0.202±0.007 and the average value of color liking 3.29; taste 3.55; and aroma 3.42 which showed liking criteria. Based on total LAB, pH and TAT, the quality of this product has met the Indonesian National Standard (SNI) for probiotic drinks, so it can be used as a probiotic drink.